MURȂBAHAB LI AL-AMR BI AL-SHIRȂ’ - Moh. Asra; Arif Hariyanto (LP2M Universitas Ibrahimy, 2019)
Islam is a religion that was revealed by the Creator to this world as a blessing for the universe. Islam is a comprehensive religion that regulates all aspects of human life; also the issue of transaction or mu’amalah. The basic concept of Islam in muamalah activities is also very concerned to the values ​​of humanism. One of the schemes of fiqh in Islamic business activities is murâbahah transactions. murâbahah transactions (both gain profit) is one of the practices that many people do. In the perspective of fiqh, murâbahah is one of the forms of buying and selling that are amânah (bay’ al-amânah). Murâbahah is generally different from other forms of buying and selling. This business practice is in great demand by business people, because it has a low level of risk. This transaction is commonly carried out by the Prophet Muhammad, and his companions. This contract known by Islamic financial institutions as al- murâbahah li al-amr bi al-shira’ then in Islamic financial institutions the term transaction becomes a banking product that is attracted by customers. According to the author, this theme is interesting to study because it is currently the most current cases of Islamic banking products. Therefore, this article will discuss the murâbahah and all matters of its discussion, in order to obtain comprehensive knowledge about murâbahah, and be useful both for writers in particular and for readers in general.